Improving the Methodology for Developing Students’ Natural and Scientific Worldview (On the Example of Teaching the Subject of “The Doctrine of Evolution”) - Atanazar Karimovich, Rakhimov (International Journal of Psychosocial Rehabilitation, 2020)
This article reveals how to improve the methodology for developing students’ natural and scientific worldviews in the process of teaching the subject of “The Doctrine of Evolution. The tasks of the research are following: clarifying the component and competency system of developing students’ natural and scientific worldview; improving the content of development of students’ natural and scientific worldview through a competency-based approach in the process of teaching the subject of “The Doctrine of Evolution”; improving the methodological structure of developing students’ natural and scientific worldview based on the integrative system of teaching the subject of “The Doctrine of Evolution”; identifying the didactic possibilities of developing students’ natural and scientific worldview in the process of teaching “The Doctrine of Evolution” and the facilitation technologies for preparing students to research activities; developing a set of non-standard educational and test tasks of a reproductive, productive, partly research and creative nature as well as electronic resources and educational and methodological support for developing students’ natural and scientific worldview in accordance with requirements of international assessment programs. The object of the research was the process of developing students’ natural and scientific worldview. 556 students of the National University of Uzbekistan, Andijan State University, Urgench State University, and Karshi State University were involved in the experiments.